Dietary supplementation with β-mannanase and probiotics as a strategy to improve laying hen's welfare - Carvalho, Camila Lopes; Andretta, Ines; Galli, Gabriela Miotto; Martins, Gabriel Bueno; Camargo, Nathalia de Oliveira Telesca; Stefanello, Thais Bastos; Melchior, Raquel; da Silva, Marcos Kipper (Frontiers in Veterinary Science, 2022)
A trend towards animal welfare improvement is observed in animal production, in addition to restrictions imposed on the use of antimicrobials. This study’s objective was to evaluate whether β-mannanase and probiotic supplementation can change hen`s behaviour. Light weight laying hens (36 weeks old) were housed in cages randomly allocated to one of four different treatments: control group, fed non-supplemented diets; diets supplemented with 300 g/ton of β-mannanase; diets supplemented with 50 g/ton of probiotic; or diets containing both 300 g/ton of β-mannanase and 50 g/ton of probiotic. The behaviour of 24 birds was recorded for a week using video cameras. The frequency and time of main behaviours (eating, walking, standing, sitting, drinking, and exploring) were analyzed in three periods per day (from 09:00 to 09:15; from 01:00 to 01:15, and from 04:00 to 04:15), as well as the time of other behaviours (leg-stretching and wings, scratching, wing-flapping, aggressive and non-aggressive pecks). Frequency and lesion scores were also analyzed using a visual score of three body regions: neck, tail, and cloaca; as well as comb injuries. β-mannanase was able to increase the frequency of feeding behaviour by 49% (P <0.05) and hens also spend 20% (P <0.05) more time in this behaviour compared to the control treatment. The use of probiotics also enhanced by 39% (P <0.05) the frequency and 19% the time (P <0.05) and the supplementation with combined additives was able to increase by 29% (P <0.05) the frequency and 25% (P <0.05) the time in feeding behaviour. β-mannanase and probiotics also increased the frequency and time spent exploring behaviour (P <0.05) and promoted a higher frequency in standing behaviour (P <0.05) and decreased the time spent on sitting behaviours (P <0.05). The combined additives showed less frequency and time in sitting behaviours (P <0.05), while increased wing-flapping behaviour (P <0.05). All the treatments were able to reduce pecking (P <0.05). Therefore, the addition of β-mannanase and probiotics to laying hen diets is an effective strategy to improve bird welfare.